Entransy in Phase-Change Systems - Gu, Junjie; Gan, Zhongxue; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Entransy in Phase-Change Systems summarizes recent developments in the area of entransy, especially on phase-change processes. This book covers new developments in the area including the great potential for energy saving for process industries, decreasing carbon dioxide emissions, reducing energy bills and improving overall efficiency of systems. This concise volume is an ideal book for engineers and scientists in energy-related industries.
Introduction -- Fundamentals of Entransy and Entransy Dissipation Theory -- Application of Entransy Theory in Thermal Storage System -- Application of Entransy Theory in Absorption Refrigeration System.
Keywords: Engineering; Renewable energy resources; Energy systems; Thermodynamics; Phase transitions (Statistical physics).; Electric power production; Heat engineering; Heat transfer; Mass transfer; Renewable energy sources; Alternate energy sources; Green energy industries; Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Energy Systems; Renewable and Green Energy; Phase Transitions and Multiphase Systems; Energy Technology; Thermodynamics